Combined global-local monitoring of hydrating concrete using embedded smart PZT sensors. (2020) - Kocherla, Amarteja; Duddi, Murali; Kolluru V.L, Subramaniam
Highlights: Development of sensor to embed inside concrete which is helpful in both EM and AR modes of sensing. The complete hydration monitoring (0 h–28 days) using local sensor along with the prediction of changes in state and stiffness of material. Correlation between EM and AR modes of sensing to understand the changes in properties of material at both local level (with in zone of influence) and bulk of the material. Discussion about orientation of sensor inside concrete and its relation to the type of stress wave generated in concrete medium. Abstract: Hydration process of concrete begins when concrete is mixed with water. Development of the early age properties of concrete are important in determining the load carrying capacity of concrete structures during construction and service. Early age monitoring of concrete is difficult due to the presence of moisture and the highly alkaline environment inside concrete. In-situ monitoring large volume of concrete in structures requires a large number of robust sensors. In this study, an embedded PZT sensor, which can be placed inside concrete and has protection from alkaline and moist environment of concrete is developed. An array of PZT sensors are placed inside a concrete structure at the time of casting (0-hour) for monitoring changes in the material over a 28-day period. The PZT sensors are used in localized and distributed sensing modes. The localized sensing is based on monitoring the changes in the electrical impedance (EI) of an embedded PZT sensor. Changes in EI measurements are shown to sensitively reflect the changes in hydrating concrete as it transforms from a fluid to a solid state and during the strength gain of the solid material. In the distributed measurement, PZT sensors are used as actuator-receiver (AR) pairs for global monitoring of concrete. The changes in the stress-waves propagating through the concrete produced by changes in the material medium are monitored. The changes in the hydrating concrete along the stress wave travelling path are sensitively reflected in AR measurements. The EI and the AR measurements techniques are combined to develop an effective methodology for monitoring the early age changes in large volumes of concrete with less number of PZT sensors. The EI measurements are used to assess the changes in vicinity of sensor and the AR measurements are used to assess the changes in bulk of concrete, so the EM and AR measurements are correlated to infer similarity in properties of material at both local level (with in zone of influence of PZT) and global level (bulk of the material).